IMPLEMENTASI PENERIMAAN PESERTA DIDIK BARU SISTEM ZONASI SMA NEGERI DI KECAMATAN BANGKINANG KOTA - Suci Fitria Rahmadhani Z (JURNAL BUANA, 2021)
This study aims to provide an overview of the implementation of the New Student Admissions of the Public High School zoning system in Bangkinang kota district and the distribution of the house points of the new student admissions on the zoning system of Public High Schools in Bangkinang kota district which consists of 4 villages including, Langgini village, Bangkinang village, Ridan village and Kumantan village. This research uses a qualitative approach with descriptive methods, as well as a type of case study research. The location of the research was carried out in Public High School 1 and 2 Bangkinang kota, where the data sources in this study were primary data obtained from observations and interviews of the Student Representatives of each Public Senior High School in Bangkinang kota district, as well as sekundur data obtained through technical guidelines for the new student admissions. at the level of Public High Schools in Riau Province and reports on the implementation of the Admission of Public High School Students in Bangkinang District, the city for the 2020/2021 school year. The difference in the implementation of the new student admissions in 2019 and 2020 lies in the implementation of socialization which is carried out online which results in information related to the acceptance of New Students not evenly distributed to prospective new students or parents of students who are in the designated zone area.